2000
DOI: 10.1111/j.1530-0277.2000.tb02067.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain High Energy Phosphate Responses to Alcohol Exposure in Neonatal Rats: An In Vivo 31P‐NMR Study

Abstract: We conclude that acute alcohol exposure that results in peak BACs of 315 mg/dl does not alter brain high energy phosphate concentrations or pHi in neonatal rat pups, although these BACs are known to result in significant brain injury. These findings do not support hypoxia as a mechanism of alcohol-mediated brain injury during the third trimester equivalent in the rat pup model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…However, on the basis of the data from the rat model system, the developing pyramidal cells in the CA1 region are vulnerable to alcohol exposure during the third trimester equivalent period. However, in that regard, we recently conducted a study to determine whether alcohol exposure reduces intracellular high-energy phosphate concentrations, reasoning that if brain tissue is indeed rendered hypoxic by fetal alcohol exposure at the cellular level, then brain tissue adenosine triphosphate formation would be reduced (Cudd et al, 2000). We used nuclear magnetic resonance spectroscopy to assess intracellular high-energy phosphate concentrations in vivo and found that alcohol exposure in neonatal rat pups with doses as high as 4.4 g/kg did not reduce adenosine triphosphate levels, suggesting that brain tissue oxygen availability was not restricted.…”
Section: Discussionmentioning
confidence: 97%
“…However, on the basis of the data from the rat model system, the developing pyramidal cells in the CA1 region are vulnerable to alcohol exposure during the third trimester equivalent period. However, in that regard, we recently conducted a study to determine whether alcohol exposure reduces intracellular high-energy phosphate concentrations, reasoning that if brain tissue is indeed rendered hypoxic by fetal alcohol exposure at the cellular level, then brain tissue adenosine triphosphate formation would be reduced (Cudd et al, 2000). We used nuclear magnetic resonance spectroscopy to assess intracellular high-energy phosphate concentrations in vivo and found that alcohol exposure in neonatal rat pups with doses as high as 4.4 g/kg did not reduce adenosine triphosphate levels, suggesting that brain tissue oxygen availability was not restricted.…”
Section: Discussionmentioning
confidence: 97%
“…This finding, coupled with reports by others that fetal haemoglobin concentration is not altered in response to ethanol (Richardson et al 1985; Gleason & Hotchkiss, 1992), provides convincing evidence that oxygen delivery to the brain is not compromised during the third trimester equivalent at these BECs. Further, previous studies have demonstrated in rats during the third trimester equivalent that ethanol doses capable of reducing fetal cerebellar Purkinje cell number do not alter global brain intracellular high‐energy phosphate concentrations (Cudd et al 2000), an indication that brain oxygenation is not altered and that ethanol does not mediate hypoxic, anaemic, ischaemic or histotoxic hypoxia. The present study is the first to demonstrate that cerebral oxygen delivery is not compromised in response to chronic binge ethanol exposure.…”
Section: Discussionmentioning
confidence: 98%